Effect of trace minerals and B vitamins on the proliferation/cytotoxicity and mineralization of a Gilthead Seabream bone–derived cell line - Viegas, Michael N. (2020)
Trace minerals and vitamins are known modulators of bone metabolism, and dietary optimization of these components may improve skeletal development and reduce the occurrence of skeleton deformities in farmed fish. As for larval stages, mineral and water-soluble vitamin nutrition requirements are lacking in research efforts and knowledge is scarce. An in vitro cell system developed from gilthead seabream vertebra and capable of mineralization was used to assess the effect of B vitamins (thiamin and pyridoxine) and trace minerals (copper, manganese, and zinc in a sulfated and chelated form) on cell proliferation and extracellular matrix (ECM) mineralization. Dependent on dose, inhibition of cellular proliferation and/or cytotoxic effects was observed for all nutrients tested and LD50 values were determined: copper, 67.4-69.5 ppm; manganese, 20.9-29.8 ppm; zinc, 37.1-42.8 ppm in sulfated and chelated form respectively; thiamin, 6273 ppm; pyridoxine, 14226 ppm. ECM mineralization was enhanced by mineral (dose and form dependent) and vitamin (dose dependent) supplementation, at non-toxic concentrations below the determined LD50s. This in vitro work confirmed the mineralogenic action of trace minerals and water-soluble vitamins and provided valuable insights for subsequent in vivo nutritional trials.